LITHOLOGY AND RESERVOIR IDENTIFICATION IN THE “EL” WELL, EAST JAVA USING SEISMIC INVERSION - Maulana Yusuf Ibrahim; Salma Dita Rysqi Puspita; Zhafirah Nurul Syarafina; Shaska Ramadhan Zulivandama; Eleonora Agustine (Marine Geological Institute of Indonesia, 2023)
The acoustic impedance inversion seismic method, carried out at the